O programa saúde na escola em municípios paranaenses na visão de gestores - Silva, Gilson Fernandes da (2016)
The School Health Program (Programa Saúde na Escola - PSE) established in 2007 by the Ministries of Health and Education, aims to increase access of the school community to health services, contribute to the integral formation of students through promotion, prevention and health care, and address vulnerabilities that could compromise the full development of children, adolescents and youth. The aim of this study was to analyze the actions for the implementation of the School Health Program in municipalities of the Regional Education Center of Cascavel / PR and the 10th Region of Health in Paraná, in the view of managers. The specific objectives were to recognize the action planning, monitoring and evaluation for the development of PSE, from the understanding of managers; characterize the actions developed in PSE in the municipal districts studied, and identify the relationship between the sectors involved in the implementation of PSE. It is an exploratory study, conducted through field research. Quantitative data were collected, available on the website of the Ministry of Education in accordance with the municipalities, and qualitative data through interviews with managers of the PSE of the Departments of Education and Health, as well as records in field diaries. Quantitative data were divided into tables and frequency tables; those that were produced in interviews and field diaries were submitted to content analysis in the form of thematic analysis. After this process the data were subjected to triangulation sources as a method of analysis. Research subjects were 15 managers, eight from the area of health, seven from education. It is important to note that among the health managers were nurses, and between education managers were pedagogues. Triangulation of sources showed the activities for planning, evaluation and monitoring of the PSE, as well as the actions undertaken in the development of PSE and the intersectoral approach experienced by managers in the development of PSE. Important to note is that the evaluation of growth and development of students is the most frequent objective set in component I. Among the PSE components, the weakest is component III, used for the training of those involved in the program, and is also the least developed and yet to be agreed. It was concluded that the PSE is deployed in the cities studied, however, at various stages. Managers say that they feel prepared for the development of PSE, which is in contradiction with the data available in SIMEC (Integrated Planning, Budget and Finance of the Ministry of Education in Brazil) where the actions for training were less evident. Municipalities have been engaged in development activities in order to ensure comprehensive care, so that the intersectoral approach has become an important strategy for the implementation of welfare and educational activities directed at the health of schoolchildren. However, the actions of component I were the most visible, which may indicate that the focus remains on the biological aspect to implement the PSE in the studied reality.